WINE INDUSTRY IN THE BEKAA VALLEY, LEBANON FOOD-PROCESSING INDUSTRY AS A BASIS FOR COMMUNITY DYNAMICS AND LOCAL SOCIO-ECONOMIC DEVELOPMENT - Antoun, Layal Bou (European Scientific Journal, ESJ, 2014)
The idea behind this paper is to counter traditional thinking on economic and social development that considers development as dependent byproduct of macroeconomic policies led by governments, or as a sole byproduct of entrepreneurial dynamics on the micro level. The idea we are defending here is that the ”Community”44 as defined by German sociologist Ferdinand Tönnies, (a tighter and more cohesive social entity) is a context where the "social" and "economic” are less separated and where the spatial dimension becomes more significant. This context could be an adequate analytical framework and a tool for regional development in the context of a developing country like Lebanon. In this context several questions arise: Could the concept of “community” be considered as an appropriate analytical framework of socioeconomic dynamics in the context of developing countries and how? What tools, does a community approach provide for regional development in Lebanon? What role do the existing tangible and intangible resources in the community play in the development process? In order to find answers to these questions, we shall employ the wine industry in the Bekaa Valley in Lebanon as a case study. After a brief background, we shall attempt, in the first section of this paper to present the socio-economic developmental situation in the Bekaa Valley. In particular, we shall focus on the agricultural sector, and examine the failure of both private and public sectors in developing this sector, and analyze the repercussions thereof. In the second section, we shall demonstrate how the wine industry not only grew, in spite of this failure, but in fact outpaced most other local agricultural activities and industries as well. Section three will examine the "community organization" surrounding the vine tree and the wine industry in the Bekaa Valley. This aspect goes beyond the economic factor, as important as this factor is in organizing the sector’s activities, to touch upon social, geographical, cultural and historical aspects too.